Self-esteem, cognitive emotion regulation strategies and depression among adult males in Kuala Lumpur, Malaysia - Hilwa Abdullah @ Mohd. Nor; Lee, Jing Giong (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aims to examine the significant difference in self-esteem, cognitive emotion regulation strategies and depression between males in early adulthood and middle adulthood. The relationships between self-esteem and cognitive emotion regulation strategies to depression are also examined. This cross-sectional study used convenience sampling technique to collect data from 180 adult male respondents in the Federal Territory of Kuala Lumpur. The inventories used in this study are Rosenberg Self-Esteem Scale (RSE) to measure the self-esteem level, Cognitive Emotion Regulation Questionnaire short version (CERQ-short) to examine the strategy that is used after experiencing negative event and Beck Depression Inventory II (BDI-II) to measure the depression level. Results show that older male adults had a higher level of self-esteem compared to younger male adults, t(178) = -1.993, p < 0.05. Younger male adults use maladaptive coping styles more often and had a higher level of depression than older male adults. Self-esteem is associated with depression significantly (r = -0.602, p < 0.01). The results could also provide information for program designed to increase the level of self-esteem and reduce the use of maladaptive coping styles in order to reduce the depression level.